Effect of abacavir on sustained virologic response to HCV treatment in HIV/HCV co-infected patients, Cohere in Eurocoord. Issue 1 (December 2015) - Smit, Colette; Arends, Joop; Peters, Lars; Montforte, Antonella; Dabis, Francois; Zangerle, Robert; Daikos, George; Mussini, Christina; Mallolas, Josep; de Wit, Stephane; Zinkernagel, Annelies; Cosin, Jaime; et al.
Abstract Background Contradicting results on the effect of abacavir (ABC) on hepatitis C virus (HCV) treatment responses in HIV/HCV co-infected patients have been reported. We evaluated the influence of ABC on the response to pegylated interferon (pegIFN) and ribavirin (RBV)-containing HCV treatment in HIV/HCV co-infected patients in a large European cohort collaboration, including data from different European countries. Methods HIV/HCV co-infected patients were included if they were aged ≥16 years, received pegIFN alfa-2a or 2b and RBV combination treatment and were enrolled in the COHERE cohort collaboration. Logistic regression was used to evaluate the impact of abacavir on achieving a sustained virologic response (SVR) to HCV treatment. Results In total 1309 HIV/HCV co-infected patients who had received HCV therapy were included, of whom 490 (37 %) had achieved an SVR. No statistically significant difference was seen for patients using ABC-containing regimens compared to patients using an emtricitabine + tenofovir (FTC + TDF)-containing backbone, which was the most frequently used backbone. In the multivariate analyses, patients using a protease inhibitor (PI)-boosted regimen were less likely to achieve an SVR compared to patients using a non-nucleoside reverse-transcriptase inhibitor (NNRTI)-based regimen (OR: 0.61, 95 % CI: 0.41–0.91). The backbone combinations zidovudine&lamivudine (AZT + 3TC) and stavudine&lamivudine (d4t + 3TC) were associated with lower SRV rates (0.45 (0.24–0.82) and 0.46 (0.22–0.96), respectively). Conclusion The results of this large European cohort study validate that SVR rates are generally not affected by ABC. Use of d4T or AZT as part of the HIV treatment regimen was associated with a lower likelihood of achieving an SVR.